Zamfira Bîrzu's artistic approach – a way to transfigure the human - Adrian Stoleriu (Anastasis: Research in Medieval Culture and Art)
book review: Zamfira Bîrzu Lazurca, Demers, Editura ARTES, Iași, 2020.